PENGARUH PROGRAM PENGALAMAN LAPANGAN (PPL) DAN PERAN GURU PAMONG TERHADAP KESIAPAN MENJADI GURU PADA MAHASISWA PROGRAM STUDI PENDIDIKAN EKONOMI ANGKATAN 2013 FKIP UNIVERSITAS SEBELAS MARET - Maulida Fajari Ningsih; Sunarto Sunarto; Jonet Ariyanto Nugroho (Department of Economics Education, Universitas Sebelas Maret, 2017)
The aims of this research are to know the existence of (1) positive and significant influence between the Field Experience Program (FEP) and the role of Mentor Teacher on the readiness in becoming a teacher of the Economic Education students in the year of 2013; (2) positive and significant influence of the Field Experience Program (FEP) on the readiness in becoming a teacher of the Economic Education students in the year of 2013; (3) positive and significant influence of the role of Mentor Teacher on the readiness in becoming a teacher of the Economic Education students in the year of 2013. This research uses quantitative descriptive with correlational method.The populations of this research are all of Economic Education students in the year of 2013 which have finished the Field Experience Program 2016 as many as 180 students consisting of 3 BKK. The sample in this research amounted to 65 students are taken by using proportional random sampling technique. The method used to collect the data is questionnaire and documentation. Those data are analyzed with multiple linear regression analysis.The result of this research shows that (1) F test value obtained Fcount > Ftable (18.765 > 3,15) with p value < 0,05 (0,000 < 0,05), so that Ho rejected and Ha accepted. It means that there is a positive and significant influence between the Field Experience Program (FEP) and the role of Mentor Teacher on the readiness in becoming a teacher of the Economic Education students in the year of 2013; (2) t test value of the Field Experience Program variable is tcount > ttable (3,957 > 1,999) with p value < 0,05 (0,000 < 0,05), so that Ho rejected and Ha accepted. It means that there is a positive and significant influence between the Field Experience Program on the readiness in becoming a teacher of the Economic Education students in the year of 2013; (3) t test value of the role of Mentor Teacher variable is tcount > ttable (2,049 > 1,999) with p value < 0,05 (0,045 < 0,05), so that Ho rejected and Ha accepted. It means that there is a positive and significant influence between the role of Mentor Teacher on the readiness in becoming a teacher of the Economic Education students in the year of 2013; (4) the coefficient of determination (R Square) is 0,377. It means that 37,7% readiness in becoming a teacher of the student are influenced by the Field Experience Program and the Mentor Teacher’s role. Meanwhile the remaining (62,3%) are influenced by other factors outside in this research. The relative contribution of the Field Experience Program and the role of Mentor Teacher on the readiness in becoming a teacher is 70,47% and 29,53%.